(untitled) (Web of Medicine: Journal of Medicine, Practice and Nursing, 2024)
This article examines the main mechanisms aimed at ensuring the liquidity of commercial banks by the Central Bank and analyzes their efficiency. The financial stability and reliability of commercial banks depends on their ability to fully satisfy their needs for liquid funds. For this reason, the mechanisms of allocating liquid funds to commercial banks by the Central Bank are of particular importance. The article analyzes the effectiveness of these mechanisms during 2020-2023.